Fat and inflammation: adipocyte-myeloid cell crosstalk in atherosclerosis - Mazitova, Aleksandra M.; Márquez-Sánchez, Ana Cristina; Koltsova, Ekaterina K. (Frontiers in Immunology, 2023)
Adipose tissue inflammation has been implicated in various chronic inflammatory diseases and cancer. Perivascular adipose tissue (PVAT) surrounds the aorta as an extra layer and was suggested to contribute to atherosclerosis development. PVAT regulates the function of endothelial and vascular smooth muscle cells in the aorta and represent a reservoir for various immune cells which may participate in aortic inflammation. Recent studies demonstrate that adipocytes also express various cytokine receptors and, therefore, may directly respond to inflammatory stimuli. Here we will summarize current knowledge on immune mechanisms regulating adipocyte activation and the crosstalk between myeloid cells and adipocytes in pathogenesis of atherosclerosis.